Emotion, social relationships, and health - Ryff, Carol D.; Singer, Burton (Series in affective science, 2001)
Social integration and affiliative relationships can be linked to a variety of health and disease outcomes. This volume gathers lines of inquiry to advance the understanding of how emotion in social relationships influences health. Social relationships have been repeatedly linked to health outcomes and even length of life, although how these effects occur remains a mystery. This volume puts forth emotion as a critical mediator of the social relationship-health nexus and presents findings from leading experts on how social emotions effect health outcomes.